Association of Type D personality and mild cognitive impairment in patients with hypertension - Ye, Qingfang; Liu, Li; Wang, Yini; Li, Ling; Wang, Zhengjun; Liu, Guojie; Lin, Ping; Li, Qiujie (Frontiers in Psychology, 2022)
Objective The aim of this study was to evaluate the association between Type D personality and mild cognitive impairment (MCI) in patients with hypertension. Methods A total of 324 subjects with hypertension were included in the study. All of them completed questionnaires on demographic characteristics, Type D personality Scale, Montreal Cognitive Assessment (MoCA), Beck Anxiety Inventory (BAI) and Beck Depression Inventory (BDI). The Type D personality effect was analyzed as both dichotomous and continuous methods. Results The incidence of MCI was 56.5% in hypertensive individuals. Type D personality presenting as a dichotomous construct was an independent risk factor of MCI (odds ratio [OR] = 2.814, 95% confidence interval [CI] = 1.577–5.021, p < 0.001), after adjusting for ages, sex and some clinical factors. Meanwhile, main effect of negative affectivity component was independently related to the prevalence of MCI (OR = 1.087, 95%CI = 1.014–1.165, p = 0.019). However, associations between the main effect of social inhibition component (OR = 1.011, 95%CI = 0.924–1.107, p = 0.811) as well as the interaction of negative affectivity and social inhibition (OR = 1.013, 95%CI = 0.996–1.030, p = 0.127) with MCI were not found. Conclusion The findings suggest that Type D personality is strongly associated with MCI in patients with hypertension. The negative affectivity component of the Type D appears to drive the correlations between Type D and MCI. These findings provide new ideas for studying the mechanisms underlying the relationship between personality and cognitive decline in hypertensive individuals.